2019
DOI: 10.12750/jarb.34.4.311
|View full text |Cite
|
Sign up to set email alerts
|

TRPV1 Is Associated with Testicular Apoptosis in Mice

Abstract: Reproductive potential decreases with age. A decrease in male fertility is due to a combination of morphological and molecular alterations in the testes. Transient receptor potential vanilloid receptor-1 (TRPV1) is associated with aging and lifespan, and its activation causes apoptotic cell death in various cell types. However, the effect of TRPV1 on testicular apoptosis in aged mice has not yet been reported. TRPV1 knockout (KO) mice had a longer lifespan than that of wild-type (WT) mice. Lifespan was increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…However, another report showed that TRPV1 KO mice have an extended lifespan and maintained youthfulness compared to WT at the same age (Riera et al, 2014). Our recent study showed that TRPV1 could induce testicular apoptosis (Siregar et al, 2019). The TRPV1 expression levels are significantly higher in the testes of older mice, with a distinct age-dependent expression pattern: a predominant expression in the Leydig cells of young adult mice and a similar level of expression throughout the testes of older mice (Siregar et al, 2019).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, another report showed that TRPV1 KO mice have an extended lifespan and maintained youthfulness compared to WT at the same age (Riera et al, 2014). Our recent study showed that TRPV1 could induce testicular apoptosis (Siregar et al, 2019). The TRPV1 expression levels are significantly higher in the testes of older mice, with a distinct age-dependent expression pattern: a predominant expression in the Leydig cells of young adult mice and a similar level of expression throughout the testes of older mice (Siregar et al, 2019).…”
Section: Introductionmentioning
confidence: 86%
“…TRPV1 KO mice have a testis phenotype with more cell death induced by oxidative stress stimuli and massive loss of germ cells from seminiferous tubules than wild-type (WT) mice Martins et al, 2014). However, another report showed that TRPV1 KO mice have an extended lifespan and maintained youthfulness compared to WT at the same age (Riera et al, 2014). Our recent study showed that TRPV1 could induce testicular apoptosis (Siregar et al, 2019).…”
Section: Introductionmentioning
confidence: 93%
“…The experimental materials and methods were used similarly to previous studies conducted in this laboratory (Siregar et al, 2019;Choe et al, 2010).…”
Section: Ethicsmentioning
confidence: 99%
“…The ovarian sections were used for immunostaining to identify the expression and localization of AQP4. The immunostaining procedures were performed as previously described (Siregar et al, 2019). Briefly, deparaffinized tissue sections were permeabilized with 0.2% Triton X-100 for 10 min at room temperature.…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%
See 1 more Smart Citation